2015
DOI: 10.1002/rsa.20628
|View full text |Cite
|
Sign up to set email alerts
|

On the threshold for the Maker‐Breaker H‐game

Abstract: Abstract. We study the Maker-Breaker H-game played on the edge set of the random graph Gn,p. In this game two players, Maker and Breaker, alternately claim unclaimed edges of Gn,p, until all the edges are claimed. Maker wins if he claims all the edges of a copy of a fixed graph H; Breaker wins otherwise. In this paper we show that, with the exception of trees and triangles, the threshold for an H-game is given by the threshold of the corresponding Ramsey property of Gn,p with respect to the graph H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 18 publications
5
33
0
Order By: Relevance
“…Next, a moment's thought shows that if a graph is 2-bounded anti-Ramsey for F , then the Breaker has a winning strategy in the Maker-Breaker F -game. Thus our result implies the result of Nenadov, Steger and Stojaković [12], where the authors have characterized edge probabilities for which a random graph is Maker's win in the Maker-Breaker Fgame. Finally, for the anti-Ramsey problem in random graphs with respect to proper-colourings we determine the lower bound for all large enough cliques and cycles.…”
Section: Introductionsupporting
confidence: 72%
“…Next, a moment's thought shows that if a graph is 2-bounded anti-Ramsey for F , then the Breaker has a winning strategy in the Maker-Breaker F -game. Thus our result implies the result of Nenadov, Steger and Stojaković [12], where the authors have characterized edge probabilities for which a random graph is Maker's win in the Maker-Breaker Fgame. Finally, for the anti-Ramsey problem in random graphs with respect to proper-colourings we determine the lower bound for all large enough cliques and cycles.…”
Section: Introductionsupporting
confidence: 72%
“…On the random geometric graph we basically have the same witness of Maker's victory, as the smallest k for which Maker can win the triangle game on edges of K k is k = 5. Interestingly, for most other graphs H it is known that a hitting time result for Maker-win in the Erdős-Rényi random graph process cannot involve the appearance of a finite graph on which Maker can win-Maker-winning strategy must be of "global nature" [18,19]. This is in contrast to the results we obtained in Theorem 1.7, showing that on the random geometric graph Maker can typically win the H-game by simply spotting a copy of one of some finite list of graphs and restricting his attention to that subgraph.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…The limiting probability is known precisely only for several special classes of graphs [18]. Recently, the order of the threshold probability was determined for all graphs H that are not trees, and whose maximum 2-density is not determined by a K 3 as a subgraph [19]. When it comes to other models of random graphs, some positional games on random regular graphs were studied in [5].…”
Section: Introductionmentioning
confidence: 99%
“…After the present work was submitted, Nenadov and Trujić [20] showed that Theorem 1.1 is true even if one replaces  k+1 by  2k+1 . Independently, a more general result was recently obtained by Antoniuk and the current authors [2].…”
Section: Note Added In Proofmentioning
confidence: 95%